2014
DOI: 10.3109/13880209.2014.946061
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided isolation of Poliovirus-inhibiting constituents fromZephyranthes candida

Abstract: The antipoliovirus activity of trisphaeridine (2) and 7-hydroxy-3',4'-methylenedioxyflavan (3) is established in this report; these compounds are of moderate toxicity and have very good SI. They could be a potential template for the development of a new antiviral agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The leaf extract of Macaranga barteri demonstrated the highest cytotoxic activity (CC 50 = 0.27 μg/mL), antiviral activity (IC 50 = 0.028 ng/mL on E7; 0.00167 ng/mL on E19) and selectivity index (SI = 7971 on E7; 130,177.50 on E19). It was observed that the cytotoxicity evaluation of the extracts seemed to correspond directly to their anti-echovirus activities, a finding similar to our earlier result [ 15 ]. Ipomoea asarifolia leaf extract also showed potent antiviral activity against E7 (IC 50 = 0.0025 μg/mL) with a high selectivity index (SI = 35,004) but was inactive against E19.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The leaf extract of Macaranga barteri demonstrated the highest cytotoxic activity (CC 50 = 0.27 μg/mL), antiviral activity (IC 50 = 0.028 ng/mL on E7; 0.00167 ng/mL on E19) and selectivity index (SI = 7971 on E7; 130,177.50 on E19). It was observed that the cytotoxicity evaluation of the extracts seemed to correspond directly to their anti-echovirus activities, a finding similar to our earlier result [ 15 ]. Ipomoea asarifolia leaf extract also showed potent antiviral activity against E7 (IC 50 = 0.0025 μg/mL) with a high selectivity index (SI = 35,004) but was inactive against E19.…”
Section: Discussionsupporting
confidence: 91%
“…Also, a wide range of flavonoids has been shown to possess antiviral activities against a variety of RNA viruses such as poliovirus, sindbis virus, respiratory syncytial virus (RSV), and DNA virus such as herpes simplex virus (HSV) [ 21 ]. The proposed antiviral mechanisms of action of flavonoids include inhibition of viral polymerase and binding of viral nucleic acid or viral capsid proteins [ 15 ]. Previous HPLC profiling of the DCM extract of M. barteri leaves revealed 3,5-dicaffeoylquinic acid, acteoside, kampferol-7- O -glucoside and bastadin-11 as its major constituents [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the fractions will be cytotoxic to cancer cell lines with very minimal toxicity to normal cells, the selectivity index (SI) of the most active fraction was determined. For in vitro studies, SI value less than 1 is classified as non-selective (toxic), between 1 and 10 is weakly selective and a SI higher than 10 is considered safe (non-toxic) [ 26 , 27 ]. From the selectivity studies, DMB had a SI value of 13.7 when compared to CTX with SI of 5.4 (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However lycorine was most active as compared to trisphaeridine and 7-hydroxy-3',4'-methylenedioxyflavan [51,52].…”
Section: Antiviral Activitymentioning
confidence: 99%